Antioxidant Activity and Characterization of the Essential oil from the Roots of Piper Marginatum Jacq. - Hurtado, Fernanda Bay; Lima, Renato Abreu; Teixeira, Leda Fabiélen; Silva, Isadora Carmo; Bay, Márcia Bay; Azevedo, Mariângela Soares; Facundo, Valdir Alves (Ciência e Natura, 2016)
Piper marginatum is traditionally known as "caapeba cheirosa" or "malvarisco", it is a medicinal plant native from Central and South America; its parts are traditionally used in folk medicine to treat stomach problems in general. Due to its importance in folk medicine and because it is a species mainly obtained by extractivism in an indiscrimante manner, this study aimed to extract, identify and quantify its fresh essential oils collected in Porto Velho, the state capital of Rondônia. The extraction of essential oil from the roots of P. marginatum was perfomed by hydrodistillation using a Clevenger graduated apparatus; the oil analysis was performed by gas chromatography with mass spectrometry. Twenty-five compounds were determined in the essential oil, among them, the (E)-anethol, (Z)-anethol, safrol, germacrene D, germacrene B, and bicyclogermacrene, showed higher levels than the other constituents in all collections and the predominant class of essential oils were the monoterpenes, sesquiterpenes and phenylpropanoids.